Disaster Risk Reduction Education Facing Climate Change in Peri-Urban Communities - Harifuddin; Syam, Syahrianti; Nurdiana; Yunianti, Nur Hadijah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Housewives are the group that feels the impact of weather changes the most, especially in suburban communities. They are trying to reduce the impact of climate change disasters on the household economy. This service is carried out to help them by offering various alternatives so that they can get out of this economic pressure. The results of implementing this service include: (1) Mapping the form of climate change disaster risk on the household economy. (2) Alternative local-based solutions to these risks. Through risk mapping and providing alternative solutions, people are stimulated and motivated to think outside the box and try more ways to solve problems. The conclusion of this service is the emergence of public awareness, especially housewives, to focus on solving household problems